Study Literatur : Pengaruh Literasi Keuangan, Pengelolaan Keuangan, dan Financial Technology terhadap Kinerja Keuangan UMKM - Shela Aprelia; Aris Eddy Sarwono (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study was conducted to examine the influence of financial literacy, financial management, and financial technology on the financial performance of MSMEs. This research method applies a literature review by analyzing and synthesizing 10 published journals related to this topic. Analysis of the study results indicates that financial literacy, financial management, and financial technology have a positive and sustainable impact on improving the financial performance of MSMEs. These findings support agency theory which focuses on the importance of monitoring and transparency in financial information reporting, and these findings also support the technology acceptance model (TAM) theory which emphasizes ease in financial services. This research provides benefits for MSME actors in managing and improving financial resources to enhance their performance